2015
DOI: 10.1007/s10616-015-9870-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cullin-RING ligases for cancer treatment: rationales, advances and therapeutic implications

Abstract: New therapeutic intervention strategies for the treatment of human malignancies are always desired. Approval of bortezomib as a front-line treatment for multiple myeloma highlighted the significance of ubiquitin-proteasome system (UPS) as a promising therapeutic target. However, due to the broad impact of proteasome inhibition, deleterious side effects have been reported with bortezomib treatment. Cullin RING ligases (CRLs)-mediated ubiquitin conjugation process is responsible for the ubiquitin conjugation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…CRLs and NAE are often particularly active in cancer cells and promote growth, survival and invasion of tumor cells. In line with this, in vitro and in vivo studies revealed anti-tumoral activity of MLN4924 in a variety of cancer models and several clinical phase I studies indicate that MLN4924 is well tolerable 17,18 . At the molecular level, the anti-tumoral effects of MLN4924 have been traced back to the inhibition of the proteasomal degradation of various negative regulators of the DNA damage response, the cell cycle and senescence 17 .…”
Section: Introductionsupporting
confidence: 52%
“…CRLs and NAE are often particularly active in cancer cells and promote growth, survival and invasion of tumor cells. In line with this, in vitro and in vivo studies revealed anti-tumoral activity of MLN4924 in a variety of cancer models and several clinical phase I studies indicate that MLN4924 is well tolerable 17,18 . At the molecular level, the anti-tumoral effects of MLN4924 have been traced back to the inhibition of the proteasomal degradation of various negative regulators of the DNA damage response, the cell cycle and senescence 17 .…”
Section: Introductionsupporting
confidence: 52%
“…Indeed, in Caenorhabditis elegans , 3′ UTRs are sufficient to specify germline-specific expression of the attached ORF ( Merritt et al, 2008 ). Even without engineering of unnatural mRNAs, it may be possible to use antisense oligonucleotides to direct splicing of poorly- or well-translated isoforms to adjust protein expression in situ ( Kole et al, 2012 ), for example to downregulate the oncogenic NAE1 gene [ Figure 5A , Xie et al, 2014 ]), which is currently being targeted by small molecules ( Luo et al, 2012 ; Wu and Yu, 2015 ). We anticipate the ability to tune the translational output of mRNA will facilitate research and therapeutic uses of designed and endogenous mRNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The HFSCs isolated from the HFs of Shaanbei White cashmere goat adults were identified, preserved, and cultured as previously described 23. Skin samples (1 cm 2 ) were clipped from the back of adult Shaanbei White cashmere goats, sterilized in 3% povidone iodine and 75% ethanol, cut into 0.5 cm × 0.5 cm segments using ophthalmic scissors, washed at least three times with phosphate-buffered saline (PBS), and then treated with 0.25% Dispase II for 14 h at 4 ºC.…”
Section: Methodsmentioning
confidence: 99%